Primary Cardiac Allograft Dysfunction—Validation of a Clinical Definition. Issue 9 (September 2015) - Dronavalli, Vamsidhar B.; Rogers, Chris A.; Banner, Nicholas R.
Abstract : Background: Heart transplantation is an established treatment for advanced heart failure. Primary allograft dysfunction (PGD) is reported in up to 40% of transplants and is associated with a poor outcome. Methods: As part of Heart Evaluation and Retrieval for Transplantation study, an investigation of the assessment of donor hearts for transplantation, we proposed a clinical definition for cardiac PGD comprising severely impaired systolic function affecting one or both ventricles accompanied by hypotension, low cardiac output, and high filling pressures occurring in the first 72 hours (in the absence of hyper acute rejection and technical surgical factors, such as cardiac tamponade). Here, we examine the prospective application of this definition to 290 heart transplants. We compared the clinical outcome of PGD and non-PGD cases. Results: Ninety-four of 290 transplants developed PGD (32.4%). Inotrope use (score) was higher in the PGD group at 24, 48, and 72 hours after transplantation ( P < 0.01). In the PGD group, there was a greater requirement for, intra-aortic balloon pump (50% vs 15%, P < 0.01), mechanical support (27% vs 0%, P < 0.01), and renal replacement therapy (61% vs 26%, P < 0.01). Intensive care stay was longer for recipients with PGD (median 14 vs 5 days, P < 0.01) and early mortality was higher (37% vs 4% at 30 days, 42% vs 8% at 1 year, P < 0.01). Conclusions: In conclusion, our definition of PGD could be applied in a national multicenter study, and the cases it defined had more frequent complications and higher mortality. Abstract : Classification of primary cardiac allograft dysfunction into three grades has been shown to be predictive of 30-day mortality in a prospective study of 290 heart transplants. This demonstrated that the classification system would be applicable for use in multicenter studies.